2019
DOI: 10.2147/vhrm.s200699
|View full text |Cite
|
Sign up to set email alerts
|

<p>Real-World Use Of Ultrathin-Strut Biodegradable Polymer–Coated Sirolimus-Eluting Stents In Patients With Coronary Artery Disease: 6-Month Clinical Outcomes</p>

Abstract: BackgroundAlthough a number of drug-eluting stents have been developed with different design, composition, and polymers, the search for an ideal drug-eluting stent is ongoing. The Tetriflex (Sahajanand Medical Technology, Surat, India) is a newer-generation, ultrathin (60 µm) biodegradable polymer–coated sirolimus-eluting stent (SES) designed with a unique long dual Z-link on a cobalt–chromium alloy. The present registry aimed to evaluate the safety and clinical outcomes of the Tetriflex SES at 6-month post-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The Tetriflex (Sahajanand Medical Technology, Surat, India) is a new-generation, ultrathin (60 µm), biodegradable SRL-eluting stent with coating composed of a combination of hydrophilic and hydrophobic polymers for controlled and prolonged release of SRL. Clinical studies have demonstrated the safety and effectiveness of the Tetriflex stent [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Tetriflex (Sahajanand Medical Technology, Surat, India) is a new-generation, ultrathin (60 µm), biodegradable SRL-eluting stent with coating composed of a combination of hydrophilic and hydrophobic polymers for controlled and prolonged release of SRL. Clinical studies have demonstrated the safety and effectiveness of the Tetriflex stent [22].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable ST rates are observed with FlexyRap ® DES study [24] and BIOFLOW-VII registry [26], while lower rate of ST is observed when compared with other contemporary device studies [20-23, 25, 27, 28]. BioMime SES also showed lower MACE rates (0.61%) [20][21][22][23][25][26][27][28] while the rates are comparable with FlexyRap ® DES study (0.4%) [24].…”
Section: Discussionmentioning
confidence: 52%
“…Another study (FOCUS registry) involving 4,720 patients who were implanted with a cobalt-chromium SES showed the rate of 3-year MACE of 7.37%, cardiac death 3.52%, TVR 2.08%, and ST 0.72% [19]. The comparison of outcomes of current registry with other contemporary devices is summarized in Table 5 [19][20][21][22][23][24][25][26][27]. In comparison to other contemporary devices, BioMime SES showed lower rates of cardiac death and MI [20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A newer-generation, ultrathin (60 µm) DESbiodegradable polymer-coated SES has been designed to substantially minimise the ISR and MACE, including composite of cardiac death, myocardial infarction, and target-lesion revascularisation. 20 Another possible cause for ISR is the premature, untimely release of cytostatic drugs, which contribute to overdose and further delay the restoration of the endothelium. 21 The antiproliferative drugs have no specificity, which not only inhibits the proliferation of vascular SMC, but also blocks the proliferation of VEC and slows the endothelialisation in an inverse relationship.…”
Section: Techniques To Tackle In-stent Restenosismentioning
confidence: 99%